Flower Diversification Across “Pollinator Climates”: Sensory Aspects of Corolla Color Evolution in the Florally Diverse South American Genus Jaborosa (Solanaceae) - Moré, Marcela; Ibañez, Ana C.; Drewniak, M. Eugenia; Cocucci, Andrea A.; Raguso, Robert A. (Frontiers in Plant Science, 2020)
Flower phenotype may diverge within plant lineages when moving across pollination climates (geographic differences in pollinator abundance or preference). Here we explored the potential importance of pollinators as drivers of floral color diversification in the nightshade genus Jaborosa taking into account color perception capabilities of the actual pollinators (nocturnal hawkmoths vs saprophilous flies) under a geographic perspective. We analyzed the association between transitions across environments and perceptual color axes using comparative methods. Our results revealed two major evolutionary themes in Jaborosa: 1) a ‘warm subtropical sphingophilous clade’ composed of three hawkmoth-pollinated species found in humid lowland habitats, with large white flowers that clustered together in the visual space of a model hawkmoth (Manduca sexta) and a ‘cool-temperate brood-deceptive clade’ composed of largely fly-pollinated species with small dark flowers found at high altitudes (Andes) or latitudes (Patagonian Steppe), that clustered together in the visual space of a model blowfly (Lucilia sp.). Our findings suggest that the ability of plants to colonize newly formed environments during Andean orogeny and the ecological changes that followed were concomitant with transitions in flower color as perceived by different pollinator functional groups. Our findings suggest that habitat and pollination mode are inextricably linked in the history of this South American plant lineage.